2017
DOI: 10.1016/j.compfluid.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface tension on free surface flow induced by a point sink in a fluid of finite depth

Abstract: The effect of surface tension on free surface flow induced by a point sink in a fluid of finite depth. Computers & Fluids, 156. pp. 526-533.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Steady or unsteady withdrawal from a fluid of finite or infinite depth through a line sink or point sink including surface-tension effects has been the subject of considerable study. Hocking et al [12][13][14], and Forbes and Hocking [10] found that the inclusion of even a small amount of surface tension has a big influence on the final values of the maximum flow rate. They were also able to show nonuniqueness in the solution domain.…”
Section: Introductionmentioning
confidence: 99%
“…Steady or unsteady withdrawal from a fluid of finite or infinite depth through a line sink or point sink including surface-tension effects has been the subject of considerable study. Hocking et al [12][13][14], and Forbes and Hocking [10] found that the inclusion of even a small amount of surface tension has a big influence on the final values of the maximum flow rate. They were also able to show nonuniqueness in the solution domain.…”
Section: Introductionmentioning
confidence: 99%